Digital Marketing in Yemen: Opportunities and Challenges - Sakher Farea Ghaleb Algonaid; Hani Gamil Mohammed Murshed (Cita konsultindo, 2025)
In light of the rapidly accelerating global digital transformation, digital marketing has emerged as one of the most important economic and social pillars of the 21st century. This research aims to explore the reality of digital marketing in Yemen, a country experiencing a protracted humanitarian and economic crisis. It analyzes the opportunities this field can provide to enhance economic activity and empower small and medium enterprises (SMEs), alongside the fundamental challenges that hinder its spread and effectiveness. Using a descriptive-analytical methodology, the study examines economic, technical, legal, and social aspects. The research concludes that digital marketing represents a strategic opportunity to overcome geographical and logistical constraints, open new markets, and create job opportunities. However, it faces significant challenges, including weak digital infrastructure, a skills gap, the absence of a regulatory legal framework, and widespread digital illiteracy. The research recommends the adoption of national policies and strategies to promote digital marketing, offering practical recommendations for government entities, educational institutions, companies, and individuals to maximize benefits and mitigate risks. It emphasizes that investment in this field is not a luxury but an imperative necessity for survival and growth in the contemporary economy.